UPAYA KETUA SEBAGAI PIMPINAN DALAM MENINGKATKAN MUTU PENDIDIKAN - Rini Ardista (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2016)
Improving the ability to manage and develop universities is essential, including the use of quality oriented modern management principles, including the application of quality-oriented modern managerial principles. To the university managers, the quality management system is based on continuous improvement to strengthen and improve. The monetary crisis and the free market have urged us to be better able to determine the future based on SWOT analysis.